Principalities and powers : revising John Howard Yoder's sociological theology - Pitts, Jamie (Cambridge, United Kingdom : Lutterworth Press, 2014)
The present book is an attempt to grapple with Yoder's critics in order to decide how to move forward with a revised ""Yoderian"" theology. Pitts suggests how that revision should be accomplished by first providing an overview of the current state of Yoder scholarship and this book's place within it; then proposing an argument that Yoder's theology can profitably read as a ""sociological theology"" that exhibits reductive tendencies, but which can be revised to be non-reductive; and finally offering an outline and justification of the proposed method of revision, which involves putting Yoder's.
Introduction -- Revising Yoder's theology of creation -- Revising Yoder's theological anthropology -- Revising Yoder's theology of violence -- Revising Yoder's theological method -- Revising Yoder's ecclesial politics -- Revising Yoder's theology of Christian particularity -- Conclusion.
Title from PDF title page (viewed on Sept. 9, 2014).
Revision of the author's thesis (Ph. D.)--University of Edinburgh, 2011.
Includes bibliographical references (pages 201-224).
Master record variable field(s) change: 072
Keywords: Yoder, John Howard; Bourdieu, Pierre, -- 1930-2002.; Theology; Powers (Christian theology) -- History of doctrines -- 20th century; Power (Christian theology) -- History of doctrines -- 20th century; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; RELIGION / Faith; Electronic books